Pyoderma Gangrenosum with an Underlying Leukocyte Adhesion Deficiency Type 1 (LAD-1) and Pregnancy in the Shade of COVID-19 Epidemic: A Patient and Physician Experience - Opalińska, Aleksandra (Dermatol Ther (Heidelb), 2021)
In the first part of this article, the anonymous patient diagnosed with leukocyte adhesion deficiency type 1 (LAD-1) and pyoderma gangrenosum (PG) discusses her experience of her medical history and treatment in a foreign country during her pregnancy and the coronavirus disease-19 (COVID-19) pandemic. The patient’s dermatologists, immunologist, and diagnostician refer to the epidemiology, genetics, diagnosis, morphologic manifestations, including skin lesions, treatment, and prognosis in LAD-1. The patient’s diagnostic and therapeutic process was discussed in the last part of this paper. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s13555-021-00507-x.